DESIGN MANAGEMENT AND PRESERVATION OF JEPARA CARVED FURNITURE - Mutiara, Maitri Widya; Irawan, Agustinus Purna; Marizar, Eddy Supriyatna (International Journal of Application on Economics and Business, 2024)
This research examines the role of design management in preserving Jepara carved furniture, which has historical and cultural value, but faces the challenge of adapting to global market dynamics. The research uses qualitative methods with a design management study approach. This study aims to explore how design management practices can be used to respond to these challenges while maintaining the richness of local culture. Through in-depth interviews, field observations, and using selected case studies, this research maps the current landscape of the Jepara carved furniture industry, identifies the main challenges faced by craftsmen and managers, and understands the opportunities that can be developed through the application of design management. The research results show that there is a gap between the traditional practice of making carved furniture and the need for design adaptations that are responsive to global market trends. In addition, this research also found that the lack of an integrated design management strategy limits the Jepara carved furniture industry's ability to innovate and compete. Based on these findings, this research proposes a design management framework that combines innovation strategies, interdisciplinary collaboration between designers and craftspeople, and effective marketing and distribution. The conclusion of this research emphasizes the importance of integrating design management in the Jepara carved furniture industry as a strategy for conservation. The implementation of effective design management is expected to inspire innovation, strengthen cultural identity, and pave the way for wider international recognition of Jepara carved furniture.